2003
DOI: 10.1002/jbm.a.10094
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and surface structure of chemically modified immunoisolating alginate‐PLL capsules

Abstract: Grafting of encapsulated living cells has the potential to cure a wide variety of diseases. Large-scale application of the technique, however, is hampered by insufficient biocompatibility of the capsules. A major factor in the biocompatibility of capsules is inadequate covering of the inflammatory poly-L-lysine (PLL) on the capsules' surface. In the present study, we investigate whether tissue responses against alginate-PLL capsules can be reduced by crosslinking the surface of the capsules with heparin or pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…The prevention of overgrowth was accomplished by inclusion of dexamethasone in the capsules. This is a rather different and unconventional approach since most groups, including ours [5,9,11,14,22], have focussed up to now on chemical modification of the capsules to improve the biocompatibility. However, recent new insight into the tissue responses have shown that the responses against capsules are not only initiated by the capsules chemical composition but are also caused by non-specific reactions as the consequence of surgical trauma associated with implantation of the grafts [15].…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of overgrowth was accomplished by inclusion of dexamethasone in the capsules. This is a rather different and unconventional approach since most groups, including ours [5,9,11,14,22], have focussed up to now on chemical modification of the capsules to improve the biocompatibility. However, recent new insight into the tissue responses have shown that the responses against capsules are not only initiated by the capsules chemical composition but are also caused by non-specific reactions as the consequence of surgical trauma associated with implantation of the grafts [15].…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue that has recently been described is the surface roughness of capsules. Bu¨nger et al [90] showed that alginate-PLL capsules provoke a strong tissue response in rats when capsules were implanted with a strong surface roughness as visualized by atomic force microscopy. This was plausibly caused by an inadequate interaction of the PLL molecules with the alginate at the surface of the capsules.…”
Section: Article In Pressmentioning
confidence: 98%
“…The literature reveals, however, that success has so far been limited and non-reproducible. It is thought that the inability of encapsulated islet grafts to reproducibly achieve and maintain long-term euglycaemia is related not only to insufficient immunoprotection, but also to a variety of technical and metabolic issues, including: the encapsulation process, composition/purity of the microcapsule [12], capsule size and surface structure [13,14], poor biocompatibility [15,16], and endotoxin levels of the alginate [17,18]. Furthermore, while the addition of poly-L-lysine has been used to reduce capsule porosity [19], its addition has resulted in an increased fibrotic response [15].…”
Section: Introductionmentioning
confidence: 99%